Mediación comunitaria: un Espacio de Intervención del Trabajador Social en la Comunidad San Pedro de Sosote del cantón Rocafuerte - Romero Chavez, Sandra Auxiliadora (2020)
Community mediation is a form of solution to social conflicts presented by certain groups; and requires the voluntariness of the parties to the dispute and a neutral third party who is a certified professional, according to the Arbitration and Mediation Law in article 48 mentions that to be qualified as an independent mediator, you must have the written authorization of a mediation center. The objective of the work was to describe the process of community mediation to improve working relationships in the San Pedro de Sosote community of the Canton Rocafuerte, Manabí, Ecuador, the same one that presented communication conflicts, the applied methodological design was in the field with an approach mixed, quantitative-descriptive supported by the statistical method, thus reaching what was proposed, using the techniques of observation, structured interview and as an instrument the interview guide, theoretically concluding on the aspects that influence conflicts between members of the artisan community and the local government that limit the development of the sector and the community intervention carried out by the Social Worker in the function of mediator; emphasizing the Harvard Model whose application allowed the creation of the new association that will be part of the craft union.